A case of Bartter syndrome type I with atypical presentations - Eun Hye Lee; Ju Sun Heo; Hyun Kyung Lee; Kyung Hee Han; Hee Gyung Kang; Il Soo Ha; Yong Choi; Hae Il Cheong (Korean Pediatric Society, 2010)
Bartter syndrome (BS) is an autosomal recessively inherited rare renal tubular disorder characterized by hypokalemic metabolic alkalosis and hyperreninemic hyperaldosteronism with normal to low blood pressure due to a renal loss of sodium. Genetically, BS is classified into 5 subtypes according to the underlying genetic defects, and BS is clinically categorized into antenatal BS and classical BS according to onset age. BS type I is caused by loss-of-function mutations in the SLC12A1 gene and usually manifests as antenatal BS. This report concerns a male patient with compound heterozygous missense mutations on SLC12A1 (p.C436Y and p.L560P) and atypical clinical and laboratory features. The patient had low urinary sodium and chloride levels without definite metabolic alkalosis until the age of 32 months, which led to confusion between BS and nephrogenic diabetes insipidus (NDI). In addition, the clinical onset of the patient was far beyond the neonatal period. Genetic study eventually led to the diagnosis of BS type I. The low urinary sodium and chloride concentrations may be caused by secondary NDI, and the later onset may suggest the existence of a genotype-phenotype correlation.In summary, BS type I may have phenotype variability including low urine sodium and chloride levels and later onset. A definitive diagnosis can be confirmed by genetic testing.